Fracture strength of orthodontic mini-implants - Tatiana Feres Assad-Loss; Flávia Mitiko Fernandes Kitahara-Céia; Giordani Santos Silveira; Carlos Nelson Elias; José Nelson Mucha
ABSTRACT Objective: This study aimed at evaluating the design and dimensions of five different brands of orthodontic mini-implants, as well as their influence on torsional fracture strength. Methods: Fifty mini-implants were divided into five groups corresponding to different manufactures (DEN, RMO, CON, NEO, SIN). Twenty-five mini-implants were subjected to fracture test by torsion in the neck and the tip, through arbors attached to a Universal Mechanical Testing Machine. The other 25 mini-implants were subjected to insertion torque test into blocks of pork ribs using a torquimeter and contra-angle handpiece mounted in a surgical motor. The shape of the active tip of the mini-implants was evaluated under microscopy. The non-parametric Friedman test and Snedecor's F in analysis of variance (ANOVA) were used to evaluate the differences between groups. Results: The fracture torque of the neck ranged from 23.45 N.cm (DEN) to 34.82 N.cm (SIN), and of the tip ranged from 9.35 N.cm (CON) to 24.36 N.cm (NEO). Insertion torque values ranged from 6.6 N.cm (RMO) to 10.2 N.cm (NEO). The characteristics that most influenced the results were outer diameter, inner diameter, the ratio between internal and external diameters, and the existence of milling in the apical region of the mini-implant. Conclusions: The fracture torques were different for both the neck and the tip of the five types evaluated. NEO and SIN mini-implants showed the highest resistance to fracture of the neck and tip. The fracture torques of both tip and neck were higher than the torque required to insert mini-implants.